Construction Economics: Digitalization in Construction Cost Management - Rani MK, Sobha (Digital Repository of Theses, 2025)
This research advances the theoretical understanding of digitalization's role in construction cost management by providing empirical evidence on the comparative advantages of digital tools, such as Building Information Modeling (BIM), over traditional methodologies. By addressing critical gaps in the current literature, the study highlights the practical benefits of digital adoption, offering a robust, data-driven foundation for future research in this domain. The findings emphasize the transformative impact of digital tools on cost efficiency, project timelines, and operational performance. BIM and other digital technologies streamline processes, reduce errors, and enhance collaboration among stakeholders, delivering measurable improvements in construction project outcomes. As the construction industry faces increasing demands for efficiency, sustainability, and cost optimization, this study highlights the urgent need for widespread digital integration. Practical implications derived from this research offer clear guidance for multiple stakeholders. Construction firms are urged to prioritize investments in digital tools and workforce training programs to remain competitive and achieve operational excellence. By embracing digitalization, companies can realize significant gains in cost predictability, resource optimization, and overall project success. For policymakers, this study highlights the importance of fostering a conducive environment for digital transformation. Strategic initiatives, including financial incentives, regulatory frameworks, and supportive infrastructure, are essential to accelerate the adoption of advanced technologies across the construction sector. Policies that facilitate collaboration between public and private entities can further drive innovation and efficiency. Furthermore, the research highlights the role of academic institutions in bridging the skills gap. By aligning curricula with evolving industry requirements, educational programs can equip future professionals with the technical expertise and practical knowledge necessary to thrive in a digitally advanced construction landscape. Integrating BIM and other digital tools into academic frameworks will ensure that emerging talent is prepared to meet industry challenges. In conclusion, this study provides a compelling case for digitalization as a critical driver of efficiency and cost management in construction. It offers actionable insights for firms, policymakers, and academia, collectively paving the way for a more innovative and sustainable industry future.